INTEGRATION OF CROSS-CULTURAL EXPERIENCES AND PROFESSIONAL COMPETENCIES: VIEWS FROM INTERNATIONAL EXCHANGE PROGRAMS IN HIGHER EDUCATION - Ngan, Tran Nguyen; Minh, Vo Thuy; Van, Lam Thi; Thanh, Le Minh (PEOPLE: International Journal of Social Sciences, 2018)
Encouraging hospitality students in reflective and transformative learning toward a global mindset becomes an imperative for developing their cross-culturally professional competency in preparation of the future career path development. Oversea exchange programs are among the initiatives to raise personal, professional and cultural awareness for the hospitality students in a pathway to encourage cross-cultural learning among students in similar fields. However, to what extent the development of a global mindset gained from the cross-cultural experiences could help undergraduate hospitality students gain their professional competency in terms of cultural skills in the hospitality and tourism context is the main issue to be described by this study. Content analysis has been conducted on in-depth interview data given by hospitality oversea exchange students who are both current students and graduated ones. The most popular modes of international student exchanges such as team project, assignment, presentations, and travel exchanges are taken into consideration to highlight deeper insights into a mutual interest between the cross-cultural experiences and the professional competency related cultural skills. The study reveals that cultural understanding needs to be experienced in the real setting context. Furthermore, we also discovered that cultural exchange outcomes are normally obtained in the daily informal practices instead of formal studies. However, the current study is constrained within few selected countries where students have been experienced and the current partnership between the home and host Institutions. This paper provides actionable guidelines and approach for integrating the critical component of cultural exchange program in the traditional curriculum program of hospitality.